1994
DOI: 10.1111/j.1399-302x.1994.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

The gingival immune response to periodontal pathogens in juvenile periodontitis

Abstract: A gingival explant culture system was utilized to evaluate the reactivity of local immunoglobulins produced by juvenile periodontitis tissue. Gingival explant culture supernatant fluids were screened, via a standardized dot-immunobinding assay, for antibodies reactive to: Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Campylobacter rectus, Eikenella corrodens, Peptostreptococcus micros, Peptostreptococcus anaerobius, Capnocytophaga ochracea, Eubacterium nodatum and Fusob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The tenuous nature of the link between P. anaerobius and periodontal disease is further documented by the immunological findings of another study. With a gingival explant culture system, Hall et al [21] evaluated the reactivity of local antibodies produced by juvenile periodontitis tissue. Only 2 of 73 gingival explant culture supernatant fluids demonstrated reactivity to P. anaerobius, indicating that this bacterium does not play a major role in periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The tenuous nature of the link between P. anaerobius and periodontal disease is further documented by the immunological findings of another study. With a gingival explant culture system, Hall et al [21] evaluated the reactivity of local antibodies produced by juvenile periodontitis tissue. Only 2 of 73 gingival explant culture supernatant fluids demonstrated reactivity to P. anaerobius, indicating that this bacterium does not play a major role in periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…An even higher prevalence of P. micros in the subgingival plaque of adult periodontitis patients has been reported, with 112 (91%) of 123 patients shown to harbour the organism as demonstrated by culture methods [19]. The gingival immune response to periodontal pathogens in juvenile periodontitis patients has been examined by a gingival explant culture system, with local IgG levels to P. micros shown to be elevated in these patients compared with healthy controls [20].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the induction of suppressive monocytes by F. nucleatum may result in the inhibition of host-protective immune reactions (195). Local suppression of specific antibody production by F. nucleatum may be the reason why Hall et al (116) found immunoglobulins to this bacterium in supernatant fluid from juvenile periodontitis tissues in only 1 of 75 patients, even though this microorganism is often isolated from subgingival plaque of such patients and F. nucleatum-specific antibodies have been detected in their sera (203,314). As discussed by Shenker (257), immunosuppression must be a relatively tem-porary phenomenon since many patients eventually develop a detectable humoral and/or cellular immune response to periodontal infection.…”
Section: Immunological Aspectsmentioning
confidence: 99%